The mediating role of family intimacy: negative emotions and resilience in adolescents with depressive disorders - Li, Chunlan; Shang, Chaona; Wang, Yuge; Yang, Lina; Pan, Miao (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the relationship between family intimacy, negative emotions and psychological resilience in adolescent inpatients with depressive disorders.MethodsThe family intimacy, adaptability scale, adolescent psychological resilience scale and positive and negative emotion scale were used to investigate 215 adolescents with depressive disorders who were hospitalized through convenience sampling method.Results①0; There was a significant positive correlation between family intimacy and psychological resilience in adolescents with depressive disorders (r = 0.456, P < 0.01); ①1; There was a significant negative correlation between negative emotions and psychological resilience in adolescents with depressive disorders (r = -0.543, P < 0.01); ①2; There was a significant negative correlation between negative emotions and family intimacy in adolescents with depressive disorders (r = -0.260, P < 0.01); ①3; Negative emotions in adolescents with depressive disorders not only had a significant negative predictive effect on psychological resilience (β = -0.878, t = -9.445, P < 0.001), but also had a significant negative predictive effect on psychological resilience through family intimacy (β = -0.736, t = -8.275, P < 0.001) Negative emotions in adolescents with depressive disorders had a significant negative predictive effect on family intimacy (β = -0.338, t = -3.936, P < 0.001); ①4; Family intimacy played a partial mediating role between negative emotions and psychological resilience, and the mediating effect accounted for 16.17% of the total effect.ConclusionReducing negative emotions and strengthening family intimacy can improve the level of psychological resilience of patients, thereby reducing self-injury and suicide in adolescents with depressive disorders.